Regulation of bile acid metabolism in biliary atresia: reduction of FGF19 by Kasai portoenterostomy and possible relation to early outcome. (11th February 2020) - Johansson, H.; Svensson, J. F.; Almström, M.; Van Hul, N.; Rudling, M.; Angelin, B.; Nowak, G.; Fischler, B.; Ellis, E.
Abstract: Background: Fibroblast growth factor 19 (FGF19) is produced in the small intestine and is involved in suppression of hepatic bile acid (BA) synthesis. FGF19 is also expressed in the liver and serum levels are elevated in adults with cholestatic liver disease. This may reflect a rescue mechanism to dampen liver injury caused by increased intrahepatic BAs. Objectives: To examine circulating FGF19 at early stages of biliary atresia and at short‐term follow‐up post‐Kasai portoenterostomy (KPE) in relation to noncholestatic infants. The relationship between FGF19, BAs and markers for BA synthesis and hepatic gene expression of factors involved in BA metabolism were also evaluated. Methods: Liver tissue, portal and peripheral blood samples were obtained from fifteen patients at KPE; additional blood was collected 4–6 months after surgery. Two control groups were included; to examine possible changes related to surgery and to compare FGF19 in biliary atresia to noncholestatic infants. Results: Circulating FGF19 levels correlated to its hepatic gene expression at time of KPE in biliary atresia and levels were elevated compared to noncholestatic infants. At follow‐up, FGF19 levels were markedly reduced, and the decline coincided with reductions in bilirubin and conjugated chenodeoxycholic acid and with increased levels of the BA synthesis marker C4. Conclusion: Elevated circulating FGF19 in biliary atresia is of hepatic origin and reduced following KPE. Changes in serum FGF19 may reflect the level of restoration of the enterohepatic circulation, and this warrants further long‐term studies on the role of FGF19 in the cholestatic liver. Abstract :